Barriers to the use of computer-managed instruction in teaching and learning Basic Technology in Anambra State, Nigeria - Chidozie Emeka Alutu (Budapest International Research and Critics University, 2024)
The paper identified the factors that hinder the implementation of Computer-Managed Instruction (CMI) in teaching and learning Basic Technology in Anambra State, Nigeria. Consequently, this study utilized a cross-sectional survey design that sampled data from the teachers and students of schools in the state. The study involved 1,092 school students and teachers from 28 public schools in Onitsha Education Zone, providing a diverse sample. Sampling occurred in three stages, resulting in a sample size of 20 teachers and 840 students. Data were collected using a structured questionnaire validated by experts, ensuring reliability. Analysis was conducted using SPSS, ensuring robust interpretation. The study highlighted several constraints such as poor electricity supply, lack of encouragement from the school authorities, technical restraints and limited access to computers. Nevertheless, teachers and students demonstrated a high level of awareness of CMI. Furthermore, no significant differences were observed in the perceptions of barriers between teachers and students. The study underscores the importance of addressing these barriers through collaborative efforts involving stakeholders to facilitate the effective integration of CMI in Basic Technology education. Overcoming these challenges can enhance teaching and learning outcomes, fostering a digitally inclusive educational environment in Anambra State.